GROWTH PERFORMANCE AND ECONOMIC ANALYSIS OF SNAKEHEAD (CHANNA STRIATA) FISH FARMING SEMI INTENSIVE SYSTEM - Mujito, Artin Indrayati; Aulia, Deni; Umidayati, Umidayati (Jurnal Perikanan Unram, 2024)
The high market demand for snakehead fish (Channa striata) makes aquaculture activities one of the solutions to declining production in nature and increasing production of snakehead fish. Various cultivation systems are used to increase productivity while still focusing on economic benefits. This study aims to determine growth performance, survival rate, and economic analysis of snakehead fish farming cultivated with a semi-intensive system. The research method consists of 2 stages, namely nursery and growthout phase. Artificial feed in the form of pellets is used during cultivation. The nursery phase uses seeds with a size ± 1 cm (0.4 g/fish), kept in a fiber tank with a density of 10 fish/liter for 30 days. Growthout phase using seeds of size 5 – 7 cm (18 g/fish) is maintained in an earthen pond with a density of 20 fish/m2 for 150 days. The average daily growth and survival rate of snakehead fish at the nursery phase were 0.59 g/day and 87%, respectively, while at the growthout phase were 0.55 g/day and 90%. The feed conversion ratio at the growthout phase is 1.48. The percentage of feed costs in the growth out phase is the highest percentage of other costs, which is 48.8% of total operational costs. The profits obtained from snakehead nursery and growthout activities are Rp. 585,000 and Rp. 2,505,000, respectively. The results of this study show that semi-intensive snakehead fish farming shows good performance and is economically profitable so it can be developed as a solution to increase snakehead fish production.